Elementary Technical Mathematics

Published by Brooks Cole
ISBN 10: 1285199197
ISBN 13: 978-1-28519-919-1

Chapter 6 - Section 6.3 - Equations with Parentheses - Exercises: 24

Answer

y=-9

Work Step by Step

Simplifying 2(y + 1) = y + -7 Reorder the terms: 2(1 + y) = y + -7 (1 * 2 + y * 2) = y + -7 (2 + 2y) = y + -7 Reorder the terms: 2 + 2y = -7 + y Solving 2 + 2y = -7 + y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. 2 + 2y + -1y = -7 + y + -1y Combine like terms: 2y + -1y = 1y 2 + 1y = -7 + y + -1y Combine like terms: y + -1y = 0 2 + 1y = -7 + 0 2 + 1y = -7 Add '-2' to each side of the equation. 2 + -2 + 1y = -7 + -2 Combine like terms: 2 + -2 = 0 0 + 1y = -7 + -2 1y = -7 + -2 Combine like terms: -7 + -2 = -9 1y = -9 Divide each side by '1'. y = -9 Simplifying y = -9
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.